2020
DOI: 10.1186/s12894-020-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

Does urethral length affect continence outcomes following robot assisted laparoscopic radical prostatectomy (RALP)?

Abstract: Background Post-operative urinary incontinence is a significant concern for patients choosing to undergo a radical prostatectomy (RP) for treatment of prostate cancer. The aim of our study was to determine the effect of pre-operative MUL on 12 month continence outcomes in men having robot-assisted laparoscopic prostatectomy (RALP). Methods We use the South Australian Prostate Cancer Clinical Outcomes Collaborative (SA-PCCOC) database, to identify 602 patients who had undergone RALP by a high volume surgeon. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
(17 reference statements)
0
17
0
2
Order By: Relevance
“…1 Interestingly, a shorter MUL before RP, is not a risk factor for preprostatectomy UI. 9 PPI is normally managed conservatively in the first instance, with fluid management advice and pelvic floor muscle training. 2 Only a small proportion of patients suffering from PPI require surgical management, usually in the form of an artificial urinary sphincter (AUS) or male sling (MS).…”
Section: Introductionmentioning
confidence: 99%
“…1 Interestingly, a shorter MUL before RP, is not a risk factor for preprostatectomy UI. 9 PPI is normally managed conservatively in the first instance, with fluid management advice and pelvic floor muscle training. 2 Only a small proportion of patients suffering from PPI require surgical management, usually in the form of an artificial urinary sphincter (AUS) or male sling (MS).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that a longer MUL was linked to early urinary continence recovery. 7,9,14,16,19 Moreover, it has been found that a longer MUL has predictive value at 12 months after RARP. 9,14 These reports were focused on urinary continence recovery to each point after RARP.…”
Section: Continence Rates According To Risk Factorsmentioning
confidence: 99%
“…7,9,14,16,19 Moreover, it has been found that a longer MUL has predictive value at 12 months after RARP. 9,14 These reports were focused on urinary continence recovery to each point after RARP. The current study was the first to examine the factors affecting urinary continence recovery in three time periods.…”
Section: Continence Rates According To Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations